Immediate and short-term outcome of balloon pulmonary valvuloplasty in neonatal critical pulmonary stenosis - Neeraj Aggarwal; Mridul Agarwal; Praneet Lale; Jay Relan; Siddartha Rudrappa; Anil Kumar; Reena Khantwal Joshi; Raja Joshi (Annals of Pediatric Cardiology)
Introduction: Balloon pulmonary valvuloplasty (BPV) is the treatment of choice for valvular pulmonary stenosis (PS) in all age groups. However, there are limited data regarding its outcomes in newborns with critical PS in the current era. We are reporting the immediate and short-term outcomes of BPV in this population. Materials and Methods: The study population comprised of all neonates with critical valvular PS who underwent BPV at our center between January 2015 and December 2022. The clinical and echocardiographic data were collected retrospectively and stratified as preintervention, intervention, and follow-up. Results: Twenty-four neonates with critical PS underwent BPV at a mean age of 7.0 ± 6.8 days. The median pulmonary and tricuspid valve (TV) Z-scores were − 0.49 and − 1.50, respectively. The procedure was performed through the femoral and jugular veins in 15 (62.5%) and 4 (16.7%) patients, respectively. The pulmonary valve could be crossed only through the retrograde route (patent ductus arteriosus) in 5 (20.8%) patients. The mean balloon annulus ratio was 1.02 ± 0.12. Eleven (45.8%) patients required graded balloon dilatation. The procedure was successful in 22/24 patients. There was a significant reduction in the pulmonary peak transvalvular gradient (83.9 ± 14.4 mmHg to 18.2 ± 7.6 mmHg; P < 0.05). Follow-up showed a progressive increase in Z-scores of pulmonary and tricuspid valve. Two patients who developed restenosis had dysplastic pulmonary valves. Conclusion: Neonates undergoing BPV have good short-term outcomes with a low restenosis rate. In patients with small TV and severe regurgitation, crossing the pulmonary valve by retrograde approach (through ductus arteriosus) is an effective method.